Quality gap in maternal and newborn healthcare: a cross-sectional study in Myanmar - Hannah H Leslie; Sumiyo Okawa; Hla Hla Win; Keiko Nanishi; Akira Shibanuma; Phyu Phyu Aye; Masamine Jimba (BMJ Global Health)
Introduction Access to maternal and newborn healthcare has improved in Myanmar. However, regular contact with skilled care providers does not necessarily result in quality care. We assessed adequate contact made by women and newborns with skilled care providers, reception of high-quality care and quality-adjusted contacts during antenatal care (ANC), peripartum care (PPC) and postnatal care (PNC) in Myanmar.Methods This cross-sectional study was conducted in a predominantly urban township of Yangon and a predominantly rural township of Ayeyawady in March 2016. We collected data from 1500 women. We measured quality-adjusted contact, which refers to adequate contact with high-quality care, as follows: ≥4 ANC contacts and receiving 11–14 of 14 intervention items; facility-based delivery assisted by skilled care providers, receiving 7 of 7 PPC intervention items; and receiving the first PNC contact ≤24 hours postpartum and ≥2 additional contacts, and receiving 16–17 of 17 intervention items. Using multilevel logistic regression analysis with a random intercept at cluster level, we identified factors associated with adequate contact and high-quality ANC, PPC and PNC.Results The percentage of crude adequate contact was 60.9% for ANC, 61.3% for PPC and 11.5% for PNC. However, the percentage of quality-adjusted contact was 14.6% for ANC, 15.2% for PPC and 3.6% for PNC. Adequate contact was associated with receiving high-quality care at ANC, PPC and PNC. Being a teenager, low educational level, multiparity and low level in the household wealth index were negatively associated with adequate contact with healthcare providers for ANC and PPC. Receiving a maternal and child health handbook was positively associated with adequate contact for ANC and PPC, and with receiving high-quality ANC, PPC and PNC.Conclusion Women and newborns do not receive quality care during contact with skilled care providers in Myanmar. Continuity and quality of maternal and newborn care programmes must be improved.